Survival Motor Neuron Protein Participates in Mouse Germ Cell Development and Spermatogonium Maintenance - Chang, Wei-Fang (Int J Mol Sci, 2020)
The defective human survival motor neuron 1 (SMN1) gene leads to spinal muscular atrophy (SMA), the most common genetic cause of infant mortality. We previously reported that loss of SMN results in rapid differentiation of Drosophila germline stem cells and mouse embryonic stem cells (ESCs), indicating that SMN also plays important roles in germ cell development and stem cell biology. Here, we show that in healthy mice, SMN is highly expressed in the gonadal tissues, prepubertal spermatogonia, and adult spermatocytes, whereas low SMN expression is found in differentiated spermatid and sperm. In SMA-like mice, the growth of testis tissues is retarded, accompanied with gamete development abnormalities and loss of the spermatogonia-specific marker. Consistently, knockdown of Smn1 in spermatogonial stem cells (SSCs) leads to a compromised regeneration capacity in vitro and in vivo in transplantation experiments. In SMA-like mice, apoptosis and accumulation of the R-loop structure were significantly elevated, indicating that SMN plays a critical role in the survival of male germ cells. The present work demonstrates that SMN, in addition to its critical roles in neuronal development, participates in mouse germ cell and spermatogonium maintenance.